Implementation of Family Hope Program (PKH) in Palopo - Utami Ningsih Darwis (Enrichment : Journal of Management, 2022)
This study aims to determine how the application of the Family Hope Program (PKH) in Poverty Reduction in Telluwanua District. The research method used is descriptive research method with a qualitative approach. Data collection is done through observation, interviews and literature study. The theoretical approach used in this research is the policy implementation approach of Daniel Mazmanin and Paul Sabtier. The results showed that the implementation of PKH in Telluwanua District regarding the knowledge and socialization of the PKH Program carried out by officers was only carried out between PKH Program Recipients and their officers. The data collection process in determining the recipients of the PKH Program has been carried out with program procedures and provisions. However, there are still many people who should be included in the criteria as recipients of the PKH Program, but have not received it. The assistance that must be carried out by the Facilitator or PKH Officer has been carried out properly. The distribution process and PKH to PKH or RTSM recipients, experienced difficulties that were felt directly by PKH participants. In addition, there is still a lack of support from parties who are not directly involved in the program or public support.